Brain Activation of Elite Race Walkers in Action Observation, Motor Imagery, and Motor Execution Tasks: A Pilot Study - Zhang, Qihan; Zhang, Peng; Song, Lu; Yang, Yu; Yuan, Sheng; Chen, Yixin; Sun, Shinan; Bai, Xuejun (Frontiers in Human Neuroscience, 2019)
Walking plays an important role in human daily life. Many previous studies suggested that long-term walking training can modulate brain functions. However, due to measuring techniques such as fMRI, PET, with highly motion-sensitive, is difficult to record individual brain activities during the movement. This study used functional near-infrared spectroscopy (fNIRS) to measure the hemodynamic responses in the frontal-parietal cortex of four elite race walkers (experimental group, EG) and ten college students (control group, CG) during tasks involving action observation, motor imagery, and motor execution. The results showed that activation levels of the pars triangularis of Broca’s area, dorsolateral prefrontal cortex (DLPFC), premotor and supplementary motor cortex (PMC & SMC), primary somatosensory cortex (S1) and primary motor cortex (M1) in EG were significantly lower than in CG during motor execution and observation tasks, and activation of frontal eye fields (FEF) in EG was lower during motor execution task. During the motor imagery task, activation intensities of the DLPFC, FEF, PMC & SMC, and M1 in EG were significantly higher than in CG. These findings suggested that the results of motor execution and observation tasks might supported the brain efficiency hypothesis, related brain regions strengthened efficiency of neural function, but the results in motor imagery task could be attributed to the forward model of elite race walkers, which showed a reverse trend to the brain efficiency hypothesis. Additionally, the activation intensities of pars triangularis of Broca’s area decreased with the passage of time in the motor execution and imagery tasks, whereas during the action observation task, no significant differences in these regions were found. Its reflected differences of the internal processing among the tasks.